Green financing tools in Ukraine: practical aspects - Frolov, Аndrii (Herald of Economics, 2025)
Introduction. In the conditions of war, when Ukraine’s energy-generating facilities have suffered huge destruction due to massive missile attacks, green financing instruments can play a key role. Such tools help support business, population, and communities on the way to energy independence, while increasing the share of electricity generation from alternative sources and increasing the energy efficiency of local infrastructure and industries. But it is important to study the available green financing instruments in Ukraine, their practical aspects, features and potential in the context of attracting investments in the alternative energy and energy efficiency sectors.Methods. The article uses: the method of generalization (when researching the scientific works of famous scientists and researchers on selected issues); methods of analysis and synthesis (to identify green financing tools and study their features and potential); logical method (for forming conclusions) Results. Government institutions and the banking sector, international organizations, communities, and business have united in solving the problem of restoring energy stability in the country. To increase the generation of alternative energy sources and save energy consumption in the country, various green financing instruments are available: green credits, green loans, green bonds, grants, local programs. These instruments have specific conditions, a limited focus of possible areas of financing, a limit size and a circle of subjects who have access to receive it. With enormous potential to support the restoration of Ukraine’s energy system, the adequacy of these tools depends on the capability of the governmental and local authorities to ensure uninterrupted access to financing for all categories of consumers. In order to overcome the energy crisis, it is important not only to encourage businesses and communities to comprehensively use available green financing tools, but also to expand the range of their capabilities, simplifying procedures and adapting tools to the specific needs of businesses, the population, and communities. The state’s priority should be the further diversification of green financing tools, which will allow implementing the latest solutions to overcome the energy deficit and achieve the maximum effect from the specifics of specific projects and consumer needs.Discussion. In international practice, other green financing tools are beginning to develop: green mutual funds, green leasing, green insurance, green exchanges, etc., which opens up a wide field for further scientific research.